Bouea microphylla Griff. (Anacardiaceae) reinstated - Ghazalli, Mohd Norfaizal; Mohamad, Abdul Latiff; Hasran, Masrom; Yunus, Muhamad Fahmi (Malaysian Nature Society, 2016)
Bouea microphylla shows some differences from Bouea oppositifolia and is reinstated as a distinct species. Morphologically the two species are close but the former differs in its smaller leaves and fruits, inflorescence position and also the ISSR data.